CO2-EOR and storage potentials in depleted reservoirs in the norwegian continental shelf NCS - Imanovs,E; Krevor,S; Zadeh,AM (2020)
Two global challenges are an increase in carbon dioxide (CO2) concentration in the atmosphere, causing global warming and an increase in energy demand (UNFCCC, 2015; EIA, 2018). Carbon Capture and Storage (CCS) is believed to be a major technology to considerably reduce CO2 emissions (Budinis et al., 2018). Applying this technology, the anthropogenic CO2 could be injected into depleted reservoirs and permanently stored in the subsurface. However, standalone CCS projects may not be economically feasible due to CO2 separation, transportation and storage costs (Pires et al., 2011). On the other hand, one of the most efficient Enhanced Oil Recovery (EOR) methods is carbon dioxide injection (Holm, 1959). Therefore, a combination of CO2-EOR and storage schemes could offer an opportunity to produce additional oil from depleted reservoirs and permanently store CO2 in the subsurface in an economically efficient manner. In this study, a depleted sandstone reservoir located in the Norwegian Continental Shelf (NCS) is used. An innovative development scenario is considered, involving two phases: CO2 storage phase at the beginning of the project followed by a CO2-EOR phase. The objective of this paper is to evaluate the effect of different injection methods, including continuous gas injection (CGI), continuous water injection (CWI), Water Alternating Gas (WAG), Tapered WAG (TWAG), Simultaneous Water Above Gas Co-injection (SWGCO), Simultaneous Water and Gas Injection (SWGI) and cyclic SWGI on oil recovery and CO2 storage potential in the depleted reservoir. A conceptual 2D high-resolution heterogeneous model with one pair injector-producer is used to investigate the mechanisms taking place in the reservoir during different injection methods. This knowledge is applied in a fiel